Aggregate Trading Behaviour of Technical Models and the Yen-Dollar Exchange Rate 1976-2007 - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2008)
The study analyses the interaction between the trading behaviour of 1,024 moving average and momentum models and the fluctuations of the yen-dollar exchange rate. I show first that these models would have exploited exchange rate trends quite profitably between 1976 and 2007. I then show that the aggregate transactions and positions of technical models exert an excess demand pressure on currency markets since they are mostly on the same side of the market. When technical models produce trading signals almost all of them are either buying or selling, when they maintain open positions they are either long or short. A strong interaction prevails between exchange rate movements and the transactions triggered by technical models. An initial rise of the exchange rate due to news, e.g., is systematically lengthened through a sequence of technical buy signals.
Keywords: 330; Exchange rate; Technical Trading; Speculation; Heterogeneous Agents; Währungsspekulation; Yen; US-Dollar; Anlageverhalten; Kapitaleinkommen; Wechselkurs; Volatilität; Schätzung; Welt